EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS), GROUP INVESTIGATION (GI), DAN PROBLEM BASED LEARNING (PBL) PADA MATERI POKOK BANGUN RUANG DITINJAU DARI KEMAMPUAN SPASIAL SISWA KELAS VIII SMP NEGERI SE-KOTA SURAKARTA - Putra P, Heldy Ramadhan; Budiyono, Budiyono; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of research were to find out: (1) which one have better learning achievement, the students receiving TPS, those receiving GI or those receiving PBL learning models, (2) which one have better learning achievement, the students with high, those with medium or those with low spatial ability, (3) in each learning model, which one have better learning achievement, the students with high, those with medium or those with low spatial ability, and (4) in each spatial ability, which one have better learning achievement, the students receiving TPS, those receiving GI or those receiving PBL learning models. This study was a quasi-experimental research with a 3 x 3 factorial design. The population of research was all of the 8th graders of Public Junior High School throughout Surakarta City. The sample was taken using stratified cluster random sampling. The instruments used for collecting data were mathematics learning achievement and spatial ability tests. Before used for data collection, the instruments of achievement and spatial ability tests were tried out first. Technique of analyzing data used was a two-way analysis of variance test with unbalancedÂ cells. Considering the result of hypothesis testing, the following conclusions could be drawn. (1) PBL type of cooperative learning have better learning achievement than the GI and TPS types did, GI type have learning achievement as good as the TPS type did. (2) The students with high spatial ability have better learning achievement than those with medium and those with low spatial ability, while those with medium spatial ability have better learning achievement than those with low spatial ability. (3) In various learning models, the students with high spatial ability have better learning achievement than those with medium and those with low spatial ability, while those with medium spatial ability have better learning achievement than those with low spatial ability. (4) In each category of spatial ability, the students receiving PBL type of cooperative learning have better learning achievement than those receiving GI and TPS types did, those receiving GI type have learning achievement as good as those receiving TPS type did.Keywords: TPS, GI, PBL, Learning Achievement, Spatial Ability